$\left(1+x^4\right)\cdot dy+x\cdot\left(1+4y^2\right)\cdot dx=0$
$\frac{dy}{dx}=\frac{2x}{3y^2}$
$\frac{dx}{dy}=y+xy$
$dx+e^{3x}dy=0$
$factor\left(x^4+x^3-6x^2-4x+8\right)$
$\frac{dy}{dx}=\frac{3x^2+4x+2}{2\left(y+1\right)}$
$\frac{dy}{dx}=e^{3x+2y}$
Differential Equations
2. See formulas
~ 0.2 s
Get a sneak peek of step by step solutions of thousands of problems.
Go premium to unlock full solutions.
Get sleep and stress.
Save up time for your hobbies.
Join <b>150k+</b> students in problem solving.